UTILIZATION OF CASSAVA SKIN AS POC MATERIAL AND 50% NPK FOR GROWTH AND PRODUCTION OF LETTUCE (LACTUCA SATIVA L.) ON ULTISOL LAND - Hendri, Putri Hani; Ibnusina, Fedri; Arnayulis (Universitas Veteran Bangun Nusantara, 2025)
Ultisol land is one of the types of soil that is less fertile and has a high level of acidity, making it a challenge in the cultivation of horticultural plants such as lettuce (Lactuca sativa L.). The excessive use of chemical fertilizers not only has a negative impact on the environment but also degrades soil quality sustainably. Therefore, environmentally friendly innovations are needed, one of which is the utilization of household organic waste such as cassava peels as the base material for Liquid Organic Fertilizer (LOF). This study aims to determine the effect of the combination of Cassava Peel Liquid Organic Fertilizer (LOF) and 50% NPK fertilizer on the growth and production of lettuce plants in ultisol land. The research was conducted in February-March 2025 using a Randomized Block Design (RBD) with four treatments, namely without LOF (100% NPK), and cassava peel LOF with doses of 13.75 ml, 15 ml, and 16.25 ml, each combined with 50% NPK. The observed parameters include the number of leaves, leaf width, leaf length, root length, fresh weight, canopy weight, and root weight. The research results show that the application of cassava peel LOF has a significant effect on the number of leaves, leaf width, leaf length, root length, fresh weight, canopy weight, and root weight. The use of cassava peel LOF, especially at a dosage of 16.25ml, can enhance the growth and production of lettuce compared to the application of 100% NPK. This treatment can be an alternative to environmentally friendly fertilizers in marginal lands such as ultisol. Keywords: Cassava peel, Lettuce, LOF, NPK, Ultisol